(untitled) - Anthony C Winkler (Orlando, Florida, 1994)
The book provides specific information on the conventions of the research paper in a readily accessible handbook format. It explains research conventions as briefly as possible. The book partitions its expanations into digestible topics that can be read separately without any loss of continuity
Keywords: rhetoric,style